2021
DOI: 10.3390/diagnostics11081370
|View full text |Cite
|
Sign up to set email alerts
|

The Possibility of Using Bioelectrical Impedance Analysis in Pregnant and Postpartum Women

Abstract: Pregnancy is a time of significant changes occurring in the composition of a woman’s body in order to provide support for the growth and development of the foetus. Bioelectrical impedance analysis (BIA) is used to assess the body composition and hydration status. This technique represents a non-invasive, reliable, and fast clinical approach, which is well tolerated by patients. A segmental impedance measurement might be advantageous in pregnant women, particularly in late pregnancy. The purpose of this paper i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 105 publications
(206 reference statements)
0
17
0
Order By: Relevance
“…The primary strength of this study is that it examined the performance of a contemporary bioimpedance analyzer in postpartum women. We used the seca mBCA 514, which is a modern, eight-electrode, segmental multifrequency device with updated equations, that include both resistance and reactance, and it adjusts for differences in body shape, which likely improves measurement accuracy [ 9 , 12 , 13 , 19 , 20 , 21 ]. Previous studies have demonstrated that this device has highly reproducible and upright positioning, and it uses metal plates instead of gel electrodes, which makes it optimal for high-throughput use in clinical and research settings [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary strength of this study is that it examined the performance of a contemporary bioimpedance analyzer in postpartum women. We used the seca mBCA 514, which is a modern, eight-electrode, segmental multifrequency device with updated equations, that include both resistance and reactance, and it adjusts for differences in body shape, which likely improves measurement accuracy [ 9 , 12 , 13 , 19 , 20 , 21 ]. Previous studies have demonstrated that this device has highly reproducible and upright positioning, and it uses metal plates instead of gel electrodes, which makes it optimal for high-throughput use in clinical and research settings [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…BIA estimates body composition by measuring the body’s resistance to an applied current and employing population- and device-specific prediction equations [ 9 ]. Historically, BIA has been considered less accurate than other methods, especially under non-standard conditions, including certain disease states, asymmetrical body shapes, and altered hydration states [ 9 , 10 , 11 ]; however, advancements in BIA devices, such as the implementation of multi-frequency and segmental approaches, have been shown to improve BIA’s performance and robustness against deviations from the norm, such as those which occur during the postpartum period [ 9 , 12 , 13 ]. Nevertheless, there is a paucity of evidence to either support or refute the use of BIA to measure postpartum body composition.…”
Section: Introductionmentioning
confidence: 99%
“…The fat-free mass (FFM) in the body contains electrolyte-rich water and has relatively low impedance, whereas fat is devoid of fluids, having a higher impedance. The FFM is measured by extrapolation using the equation of resistance, weight, height, and sex, which are different between males and females and are validated against DXA measures (Obuchowska et al, 2021). The equation prediction for FFM in women used by the BIA foot-to-foot monitors is as follows:…”
Section: Methodsmentioning
confidence: 99%
“…In FF-BIA, the current circulates in the legs and the lower part of the trunk. FF-BIA has already been validated for measuring body fat mass in different populations (Obuchowska et al, 2021). Moreover, in this study, the total body fat was measured at 30 days postpartum to eliminate the influence of fast fluid losses observed in the early postpartum stage (Schneider-Worthington et al, 2020).…”
Section: Measurement Of Total Body Fat Compositionmentioning
confidence: 99%
“…Pregnancy is a special time for a woman, when her organism undergoes various physiological changes so that the fetus has optimal conditions for growth and development [ 1 , 2 ]. These modifications pertain also to the microflora of an expectant mother.…”
Section: Introductionmentioning
confidence: 99%